The Principle of Cooperation in Service Communication Conversations - Deavisca, Kenza Viorel; Iswatiningsih, Daroe; Faizin, Faizin; Setiawan, Arif (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research aims to (1) describe the form of compliance and language function of the principle of cooperation in service communication conversations at the Muhammadiyah University of Malang Library, 2) describe violations and factors that influence the principle of cooperation in service communication conversations at the Muhammadiyah University of Malang Library. This type of research method is qualitative with a case study research approach. The research data is about the principles of cooperation in service communication conversations at the Muhammadiyah University of Malang Library. The data source comes from primary data sources in the form of dialogue text fragments in recorded service communication conversations that occurred between students and library staff at the University of Muhammadiyah Malang. The data collection technique was carried out using the note-taking method. Then, the data analysis technique is carried out by analyzing the data by reducing the data, presenting the data, and drawing conclusions. The results of the research analysis show (1) there are four forms of compliance with the maxims of cooperation principles, which include the maxim of quantity, the maxim of quality, the maxim of relevance, and the maxim of manner. There are two language functions found in compliance with these maxims, including assertive and directive language functions. The function of assertive language, namely stating, is found in the maxim of quantity and the maxim of quality, while the function of directive language, namely commanding, is found in the maxim of relevance and the maxim of manner, (2) there are two forms of violation of the maxim of the principle of cooperation which include the maxim of quantity and the maxim of relevance. There are also factors that influence the occurrence of violations of these maxims. Violations that occur in the maxim of quantity are influenced by situational factors and conditions that are being experienced. Meanwhile, violations of the maxim of relevance are influenced by the lack of known information.